A Goal Programming Model for Budgetary Allocation of an IT Organization - Prathyusha, G.; Kumara, K. N. Udaya; Kumara, K. M. Praveena (Communications in Mathematics and Applications, 2023)
Goal Programming has become one of the renowned approaches for dealing with multi-objective decision-making challenges due to its versatility in resolving multi-objective decision-making problems. This work presents a strategy for executing an IT company’s budget allocation to achieve maximum employment benefits, organizational income, and overall costs while limiting the institution’s total budget. The proposed model has illustrates using real-world data, with the outcomes exhibiting that this model helps decision-makers by allowing for a collaborative decision-making process to enhance the planning framework and meet the objective of creating acceptable solutions.